Endoparasites Of Various Species Of Anurans In Penang Island, Peninsular Malaysia - Abdullah, Zatil Shakinah (2013)
Wild animals, including anuran are usually infected with several species of parasites. The population is often threatened by massive deaths among other things because of the dispersal and territorialism of most parasites species. Frogs are important for a variety of reasons. Firstly, they control populations of insects and secondly they can act as indicator species to the environment. Studies have shown that anurans can harbor many species of parasites. Worldwide, there are numerous researches carried out on anuran parasites but few represented from Malaysia. From this study, 300 anurans from 14 species were collected from eight study sites: Duttaphrynus melanostictus, Phrynoidis aspera, Hylarana erythraea, H. labialis, H. nigrovittata, Polypedates leucomystax, Fejervarya cancrivora, F. limnocharis, Limnonectes blythii, L. paramacrodon, L. ibanorum, L. ingeri, Microhyla butleri, and Kaloula pulchra. About 11 helminths (Heterakis sp., H. vesicularis, Trichostrongylus sp., Pharyngodon sp., Ascaris sp., Oswaldocruzia sp., Rhabdias sp., Glypthelmins staffordi, Diplodiscus sacculosus, Manodistomum sp., and Macracanthorynchus sp.), eight blood parasites (a rickettsia, Hepatozoon sp., Haemogregarina sp., Lankesterella sp., Trypanosoma loricatum, T. rotatorium, T. chattoni, and microfilaria) and one protozoa (Nyctotherus spp.) were recorded from frogs. There were correlations between the present helminth parasites and distribution of rainfall, and similarity between blood parasites and Biochemical Oxygen Demand (BOD) of water.